Relations entre la circulation profonde atlantique et l’hydrologie des régions tropicales : apport des reconstructions paléoclimatiques du Quaternaire - Govin, Aline (CCSD, 2024)
My research activities aim to better understand the mechanisms of interaction between ocean circulation, tropical and polar climate, and ice sheets during Quaternary climate changes. I am particularly interested in the variability of deep Atlantic circulation and continental hydroclimate in tropical regions (especially in South America) on different Quaternary time scales. I have a particular interest in the climate of interglacial periods, including the Last Interglacial.My research work relies on high-quality paleoclimatic reconstructions, which I endeavour to date as robustly and accurately as possible, from the analysis of marine sediments, as well as on their comparison with the output of climate simulations to refine the hypotheses of climatic mechanisms at play.These activities have led me to lead several scientific projects (including a major oceanographic cruise) and to (co-)supervise several interns, PhD students, post-docs and computer engineers. I have also taken on scientific and collective responsibilities at local, regional and national level, as well as occasional teaching and scientific dissemination missions.In the coming years, I aim to deepen our understanding of the mechanisms of variation in the hydroclimate and vegetation of tropical South America at different Quaternary time scales. I also aim to develop an ambitious project to build a reference record of the past intensity of the deep North Atlantic circulation, in order to better understand the forcings and mechanisms governing its Quaternary variability.Finally, in the long term, I would like to further contribute to national efforts to develop user-friendly, on-line and interoperable tools, which by assimilating paleoclimate reconstructions from databases and paleoclimate simulations from dedicated catalogues, will provide an integrated view of past climates and improve our understanding of the complex interactions governing the Earth's climate system. Mes activités de recherche visent à mieux comprendre les mécanismes d’interaction ...